2019
DOI: 10.1016/j.nicl.2019.101983
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effect of age and APOE-ε4 allele load on white matter myelin content in cognitively normal middle-aged subjects

Abstract: The apolipoprotein E gene (APOE) ε4 allele has a strong and manifold impact on cognition and neuroimaging phenotypes in cognitively normal subjects, including alterations in the white matter (WM) microstructure. Such alterations have often been regarded as a reflection of potential thinning of the myelin sheath along axons, rather than pure axonal degeneration. Considering the main role of APOE in brain lipid transport, characterizing the impact of APOE on the myelin coating is therefore of crucial interest, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 60 publications
2
29
0
Order By: Relevance
“…The procedure for determining the apolipoprotein (ApoE) genotype was performed as previously described ( Operto et al, 2019 ). Briefly, total DNA was obtained from the blood cellular fraction by proteinase K digestion followed by alcohol precipitation, using the QIAamp DNA Blood Maxi Kit.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure for determining the apolipoprotein (ApoE) genotype was performed as previously described ( Operto et al, 2019 ). Briefly, total DNA was obtained from the blood cellular fraction by proteinase K digestion followed by alcohol precipitation, using the QIAamp DNA Blood Maxi Kit.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, Voxel Based Morphometry (VBM) style analyses are never appropriate in T1w/T2w studies of the cerebral cortex. Skeletonized methods such as Tract-Based-Spatial-Statistics (TBSS; Smith et al, 2006) offer the best option for voxelwise white matter analysis (e.g., Operto et al, 2019), though tractography-based tract analyses would likely be even better (Chen et al, 2017; Thompson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, however, it is NOT appropriate to attempt "VBMstyle" analyses of these T1w/T2w ratio volumes in lieu of proper surface-based cortical analyses for reasons described elsewhere (Glasser et al, 2016b;Coalson et al, 2018), and also because partial volume effects of CSF, grey matter, and white matter will completely dominate the differential effects of myelin content in traditional volume-based analyses (i.e., the differences in T1w/T2w ratio between tissues are much larger than those within tissues). Skeletonized methods such as Tract-Based-Spatial-Statistics (TBSS; Smith et al, 2006) offer the best option for voxelwise white matter analysis (e.g., Operto et al, 2019), though tractography-based tract analyses would likely be even better (Chen et al, 2017;Thompson et al, 2020).…”
Section: Correction Of T1w/t2w Ratio Volumesmentioning
confidence: 99%
“…Therefore, identifying joint contribution of APOE ε4 allele and age on the brain and cognition could have a profound impact on our understanding of the underlying process that influences brain function in disease. Operto et al found a significant negative interaction between the number of APOE ε4 alelles and age in extensive bilateral regions of the WM in both the recessive and the additive contrast [19]. However, does the APOE ε4 allele moderate agerelated changes in WM fibers integrity?…”
Section: Introductionmentioning
confidence: 99%